Work-related dreams: an online survey - Schredl, Michael; Anderson, Lilian Marie; Kahlert, Lea Katharina; Kumpf, Celine Sophie (Clocks & sleep, 2020)
Professional work is an integral part of modern life. According to the continuity hypothesis of dreaming, which states that dreams reflect waking life, work-related dreams should be quite common. As most dream content analytic studies are carried out in student samples, the topic of work in dreams is understudied. A few small studies indicate that the stress levels associated with the job are especially reflected in work-related dreams. Here, a total of 1695 people (960 women, 735 men) completed an online survey that included questions about the estimated percentage of work-related dreams, the overall emotional tone of work-related dreams, and waking-life experiences related to their current job situation (working or not working). The findings indicate that every fifth dream is related to current or previous work. Individuals who are working dreamed more often about work, with jobs that are experienced as being more stressful being more likely to affect dream content. The emotional tone of work-related dreams was related to stress and the emotions related to work in waking life. Overall, the findings demonstrate that professional life has a profound effect on dreaming in many individuals—even after years. The next steps would be to study the dream content of work-related dreams and relate these contents to specific characteristics about the jobs, e.g., professional field, hierarchical position and autonomy, etc.
Gesehen am 11.11.2025